(untitled) (Simbiótica. Revista Eletrônica, 2023)
The article analyses the complex and contradictory relationships between the LGBTIQ+ movements and the institutional framework in Cuba. The regulatory and institutional framework of the island, related to these movements, is described. These movements’ main manifestations and expressions of action are shown, emphasising the last five years. Some elements of the shared social imaginary around gender and sexual dissent are also analysed. Social psychology, psychoanalysis, philosophy and social sciences, in general, are taken as a referential theoretical framework. Finally, some of the questions and challenges to be resolved between these two poles are presented: the institutional framework and the LGBTIQ+ movements in Cuba and some suggestions for research.